Identification aids for Cicer (Leguminosae, Cicereae) taxa - Coles, S.; Maxted, N.; van der Maesen, L. J. G. (Edinburgh Journal of Botany, 2010)
Identification aids for Cicer (Leguminosae, Cicereae) taxa are presented. A DELTA format dataset was generated for 42 Cicer taxa, on the basis of observation of 214 herbarium specimens and information obtained from the literature. Using the programs key, explore and confor, a dichotomous key, a tabular key, an interactive key and brief descriptions were produced and are presented.